(untitled) (Revista de Ciências Agroveterinárias, 2008)
The adjustment of stocking rate to the available forage is one of the most efficient ways to enhance sustainability of production in natural pastures. The definition of the best level of herbage allowance must consider results of animal performance, in association with aspects related to the soil. This research aimed to evaluate the physical attributes of a Paledult soil (300 g kg-1 clay) under natural pasture managed for 18 years with different grazing intensities, represented by daily herbage allowances of 4, 8, 12 and 16 kg dry matter per each 100 kg animal live weight. The effect of trampling and excreta accumulation due to the concentration of animals close to water sources was also evaluated, in comparison with areas regularly grazed. An area without grazing was included as a control. Changes in the soil attributes were observed. They were related to grazing intensity ant to other factors, such as trampling intensity and excreta distribution. Such alterations occurred mainly on the soil surface layer, where the soil density and microporosity increased, and macroporosity decreased in grazing areas compared to the no-grazed control. The diameter of stable soil aggregates was larger on herbage allowances of 8 and 12%. Results indicate that intermediate grazing intensities (8-12%) are more adequate for this environment.